Newcomers as Agents for Social Change: Learning from the Italian Experience A Recourse Book for Social Work and Social Work Education in the Field of Migration - Reich, Hannah; Di Rosa, Roberta T. (Condivisione del sapere nel servizio sociale, 2021)
This publication is a resource book for Social Workers engaging in the ﬁeld of migration. It aims to, on the one hand, display facts about the living realities on the ground migrants and Social Workers active in the ﬁeld are facing, circumstances presented by experienced practitioners and researchers of this ﬁeld. On the other hand, it presents methods and approaches, extracting them from these experiences and reﬂections insights, relevant for Social Work and consequently, also signiﬁcant for Social Work educational practice. The new challenges of the 21st century ask Social Work education for a change, adapting curricula towards more experienced based teaching practices, intercultural, participatory learning sites and exchange, and future oriented personal empowerment and resilience training. International Social Work could take on a transformational leading role, as our global security and well-being of tomorrow depends on the educational foundations laid down today.